(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
In the article the author examined the dynamic of the external national debt. We also defined the main conditions of carrying out the restructuring. Thus during the research it was discovered, that the biggest load of satisfaction of the gross external debt on the national budget was due for the year of 2015. Secondly, the USA dollar takes the first place in the structure of the currencies of the debt satisfaction that automatically has increased the amount of the debt beginning from February, 2015 because of devaluation. Moreover one of the main indicative indexes – ratio of the national debt to GNI has overstepped the extreme limit (60 %) and has become more than 90 %. In the current situation one of the alternative variants is carrying out the restructuring of the part of the external debt of Ukraine to foreign private creditors. Also among the statements of the mentioned agreement there are the following ones: - Reducing the basic amount of the debt (for 20 % or 3,8 billion USA dollars); - Some increasing of the interest rate of the debt obligations (from 7,22 to 7,75 %); - Changing the terms of the debt repayment (the terms are put off from 2015-2023 to 2019-2027); - The emission by Ukraine of new debt government securities, the rate of which is related to the GIP rate. Besides we studied important steps, which were made to improve the situation in the field of debt management of Ukraine during the last years.